2011
DOI: 10.1038/emboj.2011.418
|View full text |Cite
|
Sign up to set email alerts
|

Wnt1/βcatenin injury response activates the epicardium and cardiac fibroblasts to promote cardiac repair

Abstract: Wnts are required for cardiogenesis but the role of specific Wnts in cardiac repair remains unknown. In this report, we show that a dynamic Wnt1/βcatenin injury response activates the epicardium and cardiac fibroblasts to promote cardiac repair. Acute ischaemic cardiac injury upregulates Wnt1 that is initially expressed in the epicardium and subsequently by cardiac fibroblasts in the region of injury. Following cardiac injury, the epicardium is activated organ‐wide in a Wnt‐dependent manner, expands, undergoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
339
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(348 citation statements)
references
References 54 publications
6
339
1
2
Order By: Relevance
“…New transgenic lines, such as Tg(tcf21:catalase) without autofluorescence or heat-inducible Tg(hsp70:catalase) without leaky transgene expression are needed for determining the levels of Dusp6 and pErk by immunostaining Based on the data from others and ours, we propose that the working model for cardiac regenerative signaling comprises two main branches: the forward pro-regenerative MAPK signaling triggered by FGF and other growth factors, as recently elucidated [20,21]; and the derepression mechanism through the Duox/Nox2-H 2 O 2 -Dusp6 pathway that converges on Erk1/2 MAPK signaling primarily in the epicardium, which then activate putative soluble factors to promote myocardial regeneration (Figure 8). Such epicardial soluble factors might include Wnt1 and IGF2 that were previously shown to play an essential function in the epicardium/cardiac fibroblasts and myocardium [46][47][48][49]. During heart regeneration, the growth factor-MAPK signaling (pErk) is gradually enhanced in injured hearts from 3 to 14 dpa with the peak around 14 dpa, which induces dusp6 expression (positive induction) that in turn dephosphorylates pErk (negative feedback) (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 98%
“…New transgenic lines, such as Tg(tcf21:catalase) without autofluorescence or heat-inducible Tg(hsp70:catalase) without leaky transgene expression are needed for determining the levels of Dusp6 and pErk by immunostaining Based on the data from others and ours, we propose that the working model for cardiac regenerative signaling comprises two main branches: the forward pro-regenerative MAPK signaling triggered by FGF and other growth factors, as recently elucidated [20,21]; and the derepression mechanism through the Duox/Nox2-H 2 O 2 -Dusp6 pathway that converges on Erk1/2 MAPK signaling primarily in the epicardium, which then activate putative soluble factors to promote myocardial regeneration (Figure 8). Such epicardial soluble factors might include Wnt1 and IGF2 that were previously shown to play an essential function in the epicardium/cardiac fibroblasts and myocardium [46][47][48][49]. During heart regeneration, the growth factor-MAPK signaling (pErk) is gradually enhanced in injured hearts from 3 to 14 dpa with the peak around 14 dpa, which induces dusp6 expression (positive induction) that in turn dephosphorylates pErk (negative feedback) (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 98%
“…This study specifically validates the importance of autonomous Wls in proliferation and differentiation of dental pulp cells by gene knockout methods with Cre recombinase in vitro, showing that Wls-deficient pulp cells had a defect in proliferation and differentiation with significant reductions in the expression of key odontoblast differentiation regulators and target molecules. In general, injury activates the endogenous Wnt pathway 24,25) . In a recent pulp cavity animal model, the response to pulpal injury was similar as shown that elevating Wnt signaling by either removing a negative Wnt regulator or by providing exogenous WNT3A protein was sufficient to significantly improve the pulp cavity's repair response 22) .…”
Section: Discussionmentioning
confidence: 99%
“…20) The Wnt1/β-catenin injury response activated cardiac fibroblasts to promote cardiac repair after acute ischemic cardiac injury, preserving cardiac function. 21) In other reports, blocking of Wnt/β-catenin signaling was shown to avert adverse remodeling or improve cardiac function in animal models of myocardial infarction. [22][23][24][25] In spite of such a context-dependency, Wnt/β-catenin signaling is thought to play a pivotal role in the progression of cardiac dysfunction/heart failure.…”
Section: Wnt/β-catenin Signaling In the Heartmentioning
confidence: 97%